Phytochemical Screening and Therapeutic Effects of Binahong (Anredera cordifolia (Ten.) Steenis) Leaves - Salim, Angeline; Kristanto, Dandy Felix; Subianto, Felicia; Sundah, Janice Evita; Jamaica, Putri Avanny; Angelika, Tiara; Maulida, Nurul Fajry (Indonesia International Institute for Life Sciences, 2021)
In this review, the function of secondary metabolites in Binahong (Anredera cordifolia (Ten.) Steenis) leaves were summarized for their therapeutic effects such as antimicrobial activity, anti-inflammatory, wound healing, lowering the blood pressure, and antihyperlipidemic activity as a potential medicinal plant to treat disease. The phytochemical screening of Binahong leaves extracted by using particular solvent showed positive results to the presence of phenolic, steroid, terpenoid, alkaloid, and saponin compounds contained in the extract. The antimicrobial activity is able to disrupt cell membrane activity and inhibit bacterial growth, meanwhile anti-inflammatory ability is able to decrease anti-inflammatory agents level. It also decreases blood pressure by regulation of lipid metabolites, reduction of peripheral resistance, and upregulation of nitric oxide activity. The ethanolic extract of Binahong leaves can reduce fat deposits or layers in the endothelial cells, cholesterol, triglycerides, and low-density lipoprotein (LDL) cholesterol levels, and decrease the levels of malondialdehyde (MDA formation) from the lipid peroxidation to prevent hyperlipidemia and heart disease.